Religious experience revisited : expressing the inexpressible? - Hardtke, Thomas. (Studies in Theology and Religion, 2016)
Religious Experience Revisited explores a dilemma which has haunted the study of religion since William James. Is religion rooted in experiences? Is religion rooted in expressions? How are experiences and expressions related? The contributors to this international and interdisciplinary compilation explore the possibilities and the impossibilities of a hermeneutics of religion. Combining theology and philosophy with biblical, cultural, historical and literary studies, they examine how religious experiences and religious expressions have been entangled in the past and in the present. These entanglements call for interdisciplinary conversations in which those who study experiences and those who study expressions can learn from each other in order to carve out important and instructive spaces for the study of religion.